Case Study in Fatal Motorcycle Injury Patterns - Budiatri Retno Noormaningrum; Idha Arfianti Wiraagni; Dhiwangkoro Aji Kadarmo (Institute of Medico-legal Publications Pvt Ltd, 2021)
Crash injury is one of the leading causes of premature death globally. In Indonesia, a motorcycle crash is themain cause of road traffic injuries. As a city with a high number of motorcycles, Yogyakarta needs the rightmitigation approach based on the local characteristics. The aim of this study was to evaluate the patterns ofinjury in a fatal motorcycle crash in Yogyakarta. Data were described from five dead motorcyclists that werebrought to the mortuary of Bhayangkara Hospital.